Relationship between interincisal angles and TMJ morphology/position and trabecular structure: a retrospective study - Xiaowen Hu; Ziwei Chen; Minhua Mo; Xiaohe Zhou; Liangjiao Chen (BMC, 2024)
Abstract Background TMJ morphology/position and trabecular structure are influenced by various factors. The role of the interincisal angle, an indicator of the anterior occlusal relationship, on TMJ remains unclear. This study aims to investigate the morphology, trabecular bone structure, and position of the condyle, as well as the glenoid fossa's morphology in skeletal class II populations with different interincisal angles. Materials and methods A total of 150 adult patients with normodivergent facial types and skeletal class II malocclusions were selected and divided into three groups based on their interincisal angles: normal, small, and large angle groups. The indexes of TMJ were measured using cone-beam computed tomography (CBCT) data and analyzed using Dolphin Imaging, Mimics, and ImageJ. Results The small angle group had the smallest anteroposterior diameter (APD), while the large angle group had a greater mediolateral diameter (MLD). The large angle group exhibited significantly the largest maximum axial area, bone surface area, and bone volume (P < 0.05). Small and large angle groups exhibited greater bone trabeculae (Tb. N) and thinner trabecular thickness (Tb. Th). Compared to the normal angle group, the small angle group exhibited a larger horizontal condylar angle and smaller bilateral condylar angles on the axial plane, while the large angle group showed the opposite trend. Small and large angle groups showed a reduced vertical condyle angle on the coronal plane, with the largest reduction observed in the large angle group (P < 0.05). Small and large angle groups had higher heights of the glenoid fossa (GFH). The large angle group exhibited the greatest GFH and width of the glenoid fossa (GFW) (P < 0.05). Conclusion The large angle group had elongated oval and large condyles, and deeper glenoid fossae, while a flattened-oval and smaller condyle, and wider and shallower glenoid fossae were observed in the small angle group. Small and large interincisal angle affects the structure of condylar trabeculae, resulting in thinner Tb. Th and greater Th. N. In the condylar position, small and large angle groups exhibit condylar rotation in the axial and coronal planes. Therefore, the interincisal angle affects the morphology, position, and trabecular structure of the TMJ. This implies that we must pay attention to the impact of the interincisal angle on TMJ, and it is crucial to restore the normal interincisal angle during orthodontic treatment.